Awareness, knowledge, attitude, and practices (A-KAP) assessment of the One Health approach in health sciences education webinar series participants in select universities in the Philippines - Kristine R. Vigilla-Montecillo; Jules Christian P. Rivera; Andrew D. Montecillo; Maria Kristina G. Almonte; Maria Fe S. Bulao; John Daniel P. Ong; Domini Theresa M. Pecundo; Romeo S. Gundran; Roderick T. Salvador; Renard M. Jamora; Michael L. Tee (Journal of Global Health Reports)
# Background